Shelf-Life Prediction of Extra Virgin Olive Oils Using an Empirical Model Based on Standard Quality Tests - Claudia Guillaume; Leandro Ravetti (Journal of Chemistry)
Extra virgin olive oil shelf-life could be defined as the length of time under normal storage conditions within which no off-flavours or defects are developed and quality parameters such as peroxide value and specific absorbance are retained within accepted limits for this commercial category. Prediction of shelf-life is a desirable goal in the food industry. Even when extra virgin olive oil shelf-life should be one of the most important quality markers for extra virgin olive oil, it is not recognised as a legal parameter in most regulations and standards around the world. The proposed empirical formula to be evaluated in the present study is based on common quality tests with known and predictable result changes over time and influenced by different aspects of extra virgin olive oil with a meaningful influence over its shelf-life. The basic quality tests considered in the formula are Rancimat® or induction time (IND); 1,2-diacylglycerols (DAGs); pyropheophytin a (PPP); and free fatty acids (FFA). This paper reports research into the actual shelf-life of commercially packaged extra virgin olive oils versus the predicted shelf-life of those oils determined by analysing the expected deterioration curves for the three basic quality tests detailed above. Based on the proposed model, shelf-life is predicted by choosing the lowest predicted shelf-life of any of those three tests.